Effect of Doping Phosphorescent Material and Annealing Treatment on the Performance of Polymer Solar Cells - Zixuan Wang; Fujun Zhang (International Journal of Photoenergy)
A series of polymer solar cells (PSCs) with P3HT:PCBM or P3HT:PCBM:Ir(btpy)3 blend films as the active layer were fabricated under the same conditions. Effects of phosphorescent material Ir(btpy)3 doping concentration and annealing temperature on the performance of PSCs were investigated. The short-circuit current density (Jsc) and open-circuit voltage (Voc) are increased by adopting P3HT:PCBM:Ir(btpy)3 blend films as the active layer when the cells do not undergo annealing treatment. The increased Jsc should be attributed to the increase of photon harvesting induced by doping phosphorescent material Ir(btpy)3 and the effective energy transfer from Ir(btpy)3 to P3HT. The effective energy transfer from Ir(btpy)3 to P3HT was demonstrated by time-resolved photoluminescence (PL) spectra. The increased Voc is due to the photovoltaic effect between Ir(btpy)3 and PCBM. The power conversion efficiency (PCE) of PSCs with P3HT:PCBM as the active layer is increased from 0.19% to 1.49% by annealing treatment at 140°C for 10 minutes. The PCE of PSCs with P3HT:PCBM:Ir(btpy)3 as the active layer is increased from 0.49% to 0.95% by annealing treatment at lower temperature at 100°C for 10 minutes.